Polyoma BK Virus: An Oncogenic Virus?. (7th July 2013) - Hassan, Syed; Alirhayim, Zaid; Ahmed, Syed; Amer, Syed
Abstract : We report a case of a 65-year-old gentleman with a history of end stage renal disease who underwent a successful cadaveric donor kidney transplant four years ago. He subsequently developed BK virus nephropathy related to chronic immunosuppressant therapy. Three years later, misfortune struck again, and he developed adenocarcinoma of the bladder.